Inflammatory bowel disease: Looking beyond the tract. (August 2019) - Chams, Sana; Badran, Reina; Sayegh, Skye El; Chams, Nour; Shams, Ali; Hajj Hussein, Inaya
Inflammatory bowel disease is a chronic inflammatory condition that encompasses Crohn's disease and ulcerative colitis. Inflammatory bowel disease is not exclusive to the gastrointestinal system, as it has been identified to be associated with extraintestinal manifestations that encompass every other organ system in the human body. This review article will comprehensively review the current knowledge on extraintestinal manifestations of inflammatory bowel disease. In addition, it will discuss the recommendations for screening and surveillance for extraintestinal manifestations in these patients since early appropriate diagnosis is imperative in preventing morbidity and cancer development.